Crystal structure of the thortveitite‐related M phase, (MnxZn1–x)2V2O7 (0.75 < x < 0.913): a combined synchrotron powder and single‐crystal X‐ray study. Issue 10 (7th September 2018) - Knowles, Kevin M.; Sil, Anjan; Stöger, Berthold; Weil, Matthias
Abstract : The crystal structure of the M phase, (Mn x Zn1– x )2 V2 O7 (0.75 < x < 0.913), can be described as a distortion of the thortveitite‐type crystal structure of β‐Mn2 V2 O7 . The distortions which give rise to the M phase from the β‐Mn2 V2 O7 prototype are noticeably less pronounced than the distortions introduced when β‐Mn2 V2 O7 transforms at low temperature to α‐Mn2 V2 O7 . A twofold superstructure in the diffraction patterns of crystals of the M phase used for single‐crystal X‐ray diffraction work arises from twinning by reticular pseudomerohedry. Abstract : The determination of the crystal structure of the M phase, (Mn x Zn1– x )2 V2 O7 (0.75 < x < 0.913), in the pseudobinary Mn2 V2 O7 –Zn2 V2 O7 system for x ≃ 0.8 shows that the previously published triclinic unit‐cell parameters for this thortveitite‐related phase do not describe a true lattice for this phase. Instead, single‐crystal X‐ray data and Rietveld refinement of synchrotron X‐ray powder data show that the M phase has a different triclinic structure in the space group P with Z = 2. As prior work has suggested, the crystal structure can be described as a distorted version of the thortveitite crystal structure of β‐Mn2 V2 O7 . A twofold superstructure in diffraction patterns of crystals of the M phase used for single‐crystal X‐ray diffraction work arises from twinning by reticular pseudomerohedry. This superstructure can be described as a commensurate modulation of a pseudo‐monoclinic basis structure closely related to the crystal structure of β‐Mn2 V2 O7 . In comparison with the distortions introduced when β‐Mn2 V2 O7 transforms at low temperature to α‐Mn2 V2 O7, the distortions which give rise to the M phase from the β‐Mn2 V2 O7 prototype are noticeably less pronounced.